Characterization of Andrographis Paniculata Extract Obtained by Microwave-Assisted Extraction (MAE) Method with Radiation Time - Premy Puspitawati Rahayu; Eny Sri Widyastuti; Eka Nurwahyuni; Citra Nurma Yunita; Lukman Hakim (Jurnal Penelitian Pendidikan IPA, 2023)
The purpose of this research was to extract Andrographis paniculata using the Microwave Assisted Extraction (MAE) method at 4 radiation (4 minutes, 6 minutes, 8 minutes, and 10 minutes) and characterize the extract on phenolic content, flavonoid content, andrographolide content, antioxidant activity, and functional group using Fourier Transform Infrared Spectroscopy (FTIR). Radiation times of the MAE method had a significant effect on phenolic content, flavonoid content, andrographolide content, and antioxidant activity of Andrographis paniculata. Radiation time for 10 minutes of MAE gave higher phenolic, flavonoid, andrographolide, and antioxidant activity of Andrographis paniculata. The IR spectra of the Andrographis paniculate extract increased as the radiation time increased. The optimum radiation time was at 8 minutes with the result of phenolic content at 57.2 mg GAE /g, flavonoid content at 113.07 ppm, andrographolide at 763.47 Âµg/ml, antioxidant activity at 71.66% and the IR spectra at 1031.92 cm-1, 2945.3 cm-1, 3346.5 cm-1.